2006
DOI: 10.1111/j.1365-2583.2006.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of two glutathione S‐transferases identified from the American dog tick,Dermacentor variabilis

Abstract: Reciprocal signalling and gene expression play a cardinal role during pathogen-host molecular interactions and are prerequisite to the maintenance of balanced homeostasis. Gene expression repertoire changes during rickettsial infection and glutathione-S-transferases (GSTs) were among the genes found up-regulated in Rickettsia-infected Dermacentor variabilis. GSTs are well known to play an important part in cellular stress responses in the host. We have cloned two full-length GSTs from D. variabilis (DvGST1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 42 publications
(89 reference statements)
0
28
0
3
Order By: Relevance
“…Injury as occurs at the tick-feeding site induces oxidative stress leading to production of reactive oxygen and nitrogen species (ROS and RNS) as part of the wound healing mechanism [209] and anti-microbial defenses [210]. Several lines of research have shown that many parasites including ticks [211, 212], helminths [213], Plasmodium spp. [214], Trypanosoma spp.…”
Section: Resultsmentioning
confidence: 99%
“…Injury as occurs at the tick-feeding site induces oxidative stress leading to production of reactive oxygen and nitrogen species (ROS and RNS) as part of the wound healing mechanism [209] and anti-microbial defenses [210]. Several lines of research have shown that many parasites including ticks [211, 212], helminths [213], Plasmodium spp. [214], Trypanosoma spp.…”
Section: Resultsmentioning
confidence: 99%
“…During attachment and blood feeding, tick genes express a variety of proteins and peptides involved in the innate immune response that function to inhibit microbial infection, as well as mitigating the oxidative stress and the toxic byproducts (e.g., heme) of hemoglobin digestion. These proteins may include several stress reducing proteins such as glutathione-S-transferases (Dreher-Lesnick et al 2006), protease inhibitors, lectins and others (Lehane et al 1997;Rudenko et al 2005;Zhou et al 2006). In addition, anti-microbial peptides in ticks have been reported to be upregulated in response to microbial challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Várias enzimas antioxidantes tiveram sua expressão gênica aumentada em diferentes espécies de carrapatos em resposta à infecção por patógenos e/ou alimentação sanguínea, como é o caso da glutationa S-transferase (Mulenga et al, 2003;Rudenko et al, 2005;Dreher-Lesnick et al, 2006). Adicionalmente, observou-se que uma catalase, enzima responsável pela detoxificação do peróxido de hidrogênio, desempenha uma função importante na regulação do estresse oxidativo no intestino de R.…”
Section: Outras Moléculas Envolvidas Na Resposta Imune No Intestino Dunclassified